Constant Output-Voltage Design for Bi-Directional Wireless Power Transfer System with Multiple Stages - Jinde Wu; Zhihui Wang; Xin Dai (Energies, 2020)
For the application of wireless power transfer (WPT) technology in a robot (like the snake robot), the power is supposed to be transferred to each device across multiple robot joints. This paper proposes a multi-stage bi-directional WPT (MB-WPT) system that not only provides power to multiple loads but also increases the power transfer distance. Besides, the last stage can charge for the preceding stages by reverse power transfer. The constant output voltage can be achieved whether the power is transmitted in a forward or reverse direction, and different output voltages for each stage can be achieved to satisfy the respective voltage requirement through the parameter design method. The validity of the theoretical analysis and the feasibility of the system are verified by experiments.